2018
DOI: 10.3399/bjgp18x698561
|View full text |Cite
|
Sign up to set email alerts
|

Direct access cancer testing in primary care: a systematic review of use and clinical outcomes

Abstract: GP DA testing performs as well as, and on some measures better than, consultant triaged testing on measures of disease detection, appropriateness of referrals, interval from referral to testing, and patient and GP satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 83 publications
(87 reference statements)
2
21
1
Order By: Relevance
“…14 MDCs that retain responsibility for the patient until their symptoms are explained and managed are distinct from GP direct access (cancer) testing which leaves these actions to the GP. 15 After years of investment in cancer sitespecific urgent referral pathways, this change in thinking appeals to generalists and specialists interested in explaining symptom causation and frustrated with subspecialist silos restricted to one cancer site. But for these MDCs to function, their positioning must become established within local healthcare systems, and test access and patient flow must be liberated to allow cross-speciality referrals and shared multidisciplinary clinical responsibility.…”
Section: Explaining Symptoms Not Just Ruling In Cancermentioning
confidence: 99%
“…14 MDCs that retain responsibility for the patient until their symptoms are explained and managed are distinct from GP direct access (cancer) testing which leaves these actions to the GP. 15 After years of investment in cancer sitespecific urgent referral pathways, this change in thinking appeals to generalists and specialists interested in explaining symptom causation and frustrated with subspecialist silos restricted to one cancer site. But for these MDCs to function, their positioning must become established within local healthcare systems, and test access and patient flow must be liberated to allow cross-speciality referrals and shared multidisciplinary clinical responsibility.…”
Section: Explaining Symptoms Not Just Ruling In Cancermentioning
confidence: 99%
“…This has also been identified in an endoscopy patient experience study 58 and highlights a potential area for improvement, as previous literature has identified that a straight‐to‐test protocol results in a reduction in times to cancer diagnosis and cancer treatment 59,60 . In addition, GP direct access testing performed as well as, and on some measures better than, consultant‐triaged testing on measures of disease detection, appropriateness of referrals, interval from referral to testing, and patient and GP satisfaction 61 …”
Section: Discussionmentioning
confidence: 86%
“…59,60 In addition, GP direct access testing performed as well as, and on some measures better than, consultant-triaged testing on measures of disease detection, appropriateness of referrals, interval from referral to testing, and patient and GP satisfaction. 61 At the referral stage, whilst health-care professionals may not want to create unnecessary anxiety for patients, previous research suggests fear can actually be increased if the patient feels unclear or unprepared for the cancer referral pathway. 62,63 Patients in a previous head and neck cancer study reported that health-care professionals rarely used the word 'cancer'.…”
Section: Comparison To Previous Researchmentioning
confidence: 99%
“…Our search strategy was purposefully kept broad and included terms describing other diagnostic strategies such as direct access and fast track testing. This was done to avoid missing relevant papers because of differences in terminology, and with a view to summarising the literature for the other diagnostic strategies which has been reported elsewhere (8).…”
Section: Searchmentioning
confidence: 99%
“…CT scan or MRI, without the need to refer to or consult with a specialist with the aim of speeding up access to testing (43). A recent systematic review reported that like one-stop clinics, direct access clinics were associated with a reduction in time from referral to testing (8). Unlike one-stop clinics, however, there was no significant reduction in time from referral to diagnosis.…”
Section: Comparison With the Literaturementioning
confidence: 99%